2019
DOI: 10.2478/ats-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Histology and Brain Derived Neurotrophic Factor immunoreaction of the neurons in the corpora quadrigemina of the African grasscutter (Thryonomys swinderianus – Temminck, 1827)

Abstract: The African grasscutter is the second largest rodent in Africa, thus, a key component of the minilivestock industry. The study described the histological features and probed the distribution of Brain Derived Neurotrophic Factor (BDNF) in the corpora quadrigemina of the African grasscutter at foetal and postnatal developmental periods. Brain samples from foetuses explanted on foetal days 60 (F60) and 90 (F90) and extracted from 3 and 6-days-old pups (P3 and P6, respectively), 72-days-old juveniles (P72) and 450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…The three layers of the rostral colliculus in the neonate, juvenile and adult African giant pouched rat shown in the present study corresponded to the study conducted in the African grasscutter rostral colliculus by Ibe et al (2019). However, the migratory immature neurons of the radial glial found in the SZ of the neonate rostral colliculus in the present study was already mature in the neonates of the African grasscutter (Ibe et al, 2019). This implies that the neonate African grasscutter may have better vision than their African giant pouched rat components.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The three layers of the rostral colliculus in the neonate, juvenile and adult African giant pouched rat shown in the present study corresponded to the study conducted in the African grasscutter rostral colliculus by Ibe et al (2019). However, the migratory immature neurons of the radial glial found in the SZ of the neonate rostral colliculus in the present study was already mature in the neonates of the African grasscutter (Ibe et al, 2019). This implies that the neonate African grasscutter may have better vision than their African giant pouched rat components.…”
Section: Discussionsupporting
confidence: 88%
“…This implied that the adult caudal colliculus was most developed, followed by that of the juveniles; the neonatal caudal colliculus was still immature. These agreed with the work of Ibe et al (2019) on the African grasscutter partly, especially for the neonates and juveniles but differed in the adults. However, statistical comparison of the lengths of the central nucleus of the caudal colliculus indicated that the juvenile and adult were each better developed than the neonate.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(b)Female reproductive system3Onoja and Ezeasor (2015), Opara, 2010 Addo et al, 2003 2.Nervous system18Bhagwandin et al (2006), Byanet, Nzalak, Salami, Umosen, et al (2008), Nzalak et al (2008), Byanet et al (2009), Ajayi et al (2011), Byanet et al (2012), Obadiah and Obadiah (2014), Byanet et al (2018). Dwarika et al (2008), Mustapha et al (2015), Ibe et al (2016), Ibe et al (2017), Mustapha et al (2017), Ibe, Salami, et al (2018), Ibe, Ikpegbu, and Nlebedu (2018), Ibe, Salami, et al (2019), Ibe, Ojo, et al (2019); Ibe et al (2020) 3.Digestive system14Asibey (1974), Alongninouwa et al (1996), van der Merwe (2000), Van Zyl et al (2005), Skinner and Chimimba (2006), van der Merwe (2007), Byanet, Nzalak, Salami, Nwaogu, et al (2008), Byanet, Salami, Ali, and Onyeanusi (2008), Barnabas (2010), Byanet et al (2011), Byanet et al (2015), Igbokwe et al (2015), Samuel et al (2016), Igbokwe (2018), 4.Musculoskeletal system10Skinner and Chimimba (2006), van der Merwe (2007), Byanet and Nwaogu (2010), Olude et al (2014), Onwuama et al (2014), Bakou et al (2015), Onwuama et al (2015), Parés‐Casanova et al (2015), Samuel et al (2015), Onwuama et al (2018). 5.Respiratory system2Ajayi et al (2009), Nwaogu and Aghaebita (2010...…”
Section: Available Literature On the African Grasscutter Anatomymentioning
confidence: 99%
“…Bhagwandin et al (2006), Byanet, Nzalak, Salami, Umosen, et al (2008), Nzalak et al (2008), Byanet et al (2009), Ajayi et al (2011), Byanet et al (2012), Obadiah and Obadiah (2014), Byanet et al (2018). Dwarika et al (2008), Mustapha et al (2015), Ibe et al (2016), Ibe et al (2017), Mustapha et al (2017), Ibe, Salami, et al (2018), Ibe, Ikpegbu, and Nlebedu (2018), Ibe, Salami, et al (2019), Ibe, Ojo, et al (2019); Ibe et al (2020)…”
Section: Available Literature On the African Grasscutter Anatomymentioning
confidence: 99%